ClpP2 modulates ClpXP assembly to promote multiple pathogenic phenotypes in Pseudomonas aeruginosa - Jia Jia Zhang; Gina D. Mawla; Reed Robinson; Arielle J. Weinstein; Tania A. Baker (Proceedings of the National Academy of Sciences, 2026)
In the opportunistic pathogen Pseudomonas aeruginosa ( Pa ), ClpXP proteases selectively degrade key transcriptional regulators (TRs), enabling dynamic control over phenotypes that promote pathogenesis and virulence. Here, we report that a natural Pa variant activates multiple pathogenic phenotypes by modulating ClpXP assembly dynamics through a spontaneous hypomorphic mutation in the canonical peptidase subunit ClpP1 (ClpP1 P6L ) and its synergistic activation by the atypical peptidase subunit ClpP2. Genetics, cell-based reporter assays, and biochemical analyses reveal that ClpP1 P6L impairs ClpXP-complex formation, but that this defect is partially suppressed upon heterooligomerization with ClpP2. Consequently, ClpX, ClpP1 P6L , and ClpP2 combine to catalyze sufficient proteolysis to trigger mucoid conversion, a virulence-associated phenotype characterized by alginate overproduction. Further, ClpP1 P6L also triggers premature rhl quorum sensing, thereby upregulating the expression of additional virulence factors. These findings demonstrate that by encoding two ClpP paralogs (ClpP1 and ClpP2), Pa can adaptively modulate ClpXP assembly dynamics to adjust proteolysis and expand its phenotypic versatility. We propose that organisms that encode multiple ClpP subunits can exert finer control over regulated substrate degradation and thereby optimize their display of pathogenic traits that support opportunistic infections.